2008
DOI: 10.1007/s11896-008-9016-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Institutional Violence among Death Row Inmates: The Utility of the Sorensen and Pilgrim Model

Abstract: The (Sorensen and Pilgrim, An actuarial risk assessment of violence posed by capital murder defendants. J Crim Law Criminol 90: [1251][1252][1253][1254][1255][1256][1257][1258][1259][1260][1261][1262][1263][1264][1265][1266][1267][1268][1269][1270] 2000) actuarial model was developed to predict institutional violence among lifesentenced murderers. However, despite its presentation at capital sentencing, the model has not been validated on death row inmates specifically. This study examined the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Prior probated sentences, drug conviction offenses, sentences less than 11 years, and sentences of life without parole were excluded from the current study. -Vollum et al (2008), the current study found the S&P scale, as well as the others examined herein, to be moderately associated with potentially violent and assaultive offenses inclusive of the least serious. Unlike Buffington-Vollum et al, however, the current study found the S&P scale, as well as the other actuarial models, to be optimally related to serious assaults.…”
Section: Predictors Of Prison Violence For Former Death Row Inmatessupporting
confidence: 62%
See 1 more Smart Citation
“…Prior probated sentences, drug conviction offenses, sentences less than 11 years, and sentences of life without parole were excluded from the current study. -Vollum et al (2008), the current study found the S&P scale, as well as the others examined herein, to be moderately associated with potentially violent and assaultive offenses inclusive of the least serious. Unlike Buffington-Vollum et al, however, the current study found the S&P scale, as well as the other actuarial models, to be optimally related to serious assaults.…”
Section: Predictors Of Prison Violence For Former Death Row Inmatessupporting
confidence: 62%
“…As Table 1 reflects, several of the actuarial models (S&P, RASP-CC, RASP-Cap) were modestly successful in modeling violence at all severity levels (i.e., potential violence, assaults, and serious assaults) in their construction samples and predicting violence in other samples. Buffington-Vollum, Edens, and Keilen (2008), however, found that the S&P scale was modestly associated with general disciplinary misconduct and minor assaults, but not with serious assaults. This discrepancy is likely a function of the low prevalence (or base rates) of serious assaults.…”
Section: Actuarial Modelsmentioning
confidence: 84%